Evaluasi Program Kampung Iklim sebagai Upaya Pengelolaan Lingkungan Berkelanjutan di Kampung Airport Kecamatan Teluknaga Kabupaten Tangerang - Muhammad Miftah Farid; Juliannes Cadith (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Climate change is an urgent global challenge demanding local adaptation and mitigation. This research focuses on evaluating the sustainability of the Climate Village Program ProKlim in Kampung Airport, Teluknaga Village, Tangerang Regency. Although this location achieved national